Nomogram-based prediction of growth retardation in pediatric deletional α-thalassemia: Evidence from the Mekong Delta, Vietnam - Bui, Nghia Quang; Tran, Ngoc Bich; Ta, Tram Van; Duong, Linh My; Pham-Thi, Ngoc-Nga; Nguyen, Vinh The; Tran, Ly Cong (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Growth retardation is a common complication in children with deletional α-thalassemia. Limited epidemiological data exist on growth retardation in α-thalassemia patients from low-resource settings such as Vietnam. This study investigates the prevalence and associated factors of growth retardation in pediatric patients with α-thalassemia to inform targeted interventions.Methods: A multicenter cross-sectional study was conducted involving children with confirmed deletional α-thalassemia from August 2022 to June 2023. Clinical, laboratory, and genetic data were analyzed to identify predictors of growth retardation.Results: Growth retardation affected 17.1% of the study population. Key predictors included splenomegaly ≥ grade II (OR = 12.5; 95% CI, 1.69–92.25; p = 0.013), hemoglobin levels